Sex differences in the utilization of drugs for COVID‐19 treatment among elderly residents in a sample of Italian nursing homes. Issue 5 (28th February 2022) - Spini, Andrea; Crescioli, Giada; Donnini, Sandra; Ziche, Marina; Collini, Francesca; Gemmi, Fabrizio; Virgili, Gianni; Vannacci, Alfredo; Lucenteforte, Ersilia; Gini, Rosa; Lombardi, Niccolò; Roberto, Giuseppe
Abstract: Purpose: To describe the use of hydroxychloroquine (HCQ), azithromycin (AZI) and low‐molecular‐weight‐heparins (LMWH) by sex among elderly residents in nursing homes (NHs) of Tuscany region (Italy) during the first pandemic peak. Methods: A population‐based drug utilization study was performed linking the Tuscany Administrative Databases (TAD) to the regional COVID‐19 registry. Among elderly patients (≥ 65 years old) registered in TAD on 1st December 2019, new users of HCQ, AZI and LMWH that started the treatment during NHs stay (i.e., no dispensing of the same drug during the previous 6 months) were respectively identified in each month of observation period (December 2019–May 2020). The percentage of subjects diagnosed with COVID‐19 (COVID‐19+) on, or before, the date of first dispensing of the drug of interest was described. Results were stratified by sex (male = M; female = F). Results: New users of HCQ, AZI and LMWH were 62, 300, and 1215, respectively. About 95% of HCQ new users received the drug in April (M = 20; F = 40) of which 11 of men (55%) and 25 of women (62%) were COVID‐19+; AZI new users in April (M = 32; F = 83) were two‐fold compared to February, of which 10 of men (31%) and 30 of women (36%) were COVID‐19+; LMWH new users showed a peak in April (M = 74; F = 142), when 31% of men and 34% of women were COVID‐19 + . Conclusions: New users showed a peak during the first pandemic wave and females were over two‐fold compared to men. HCQ was often prescribed in absence of COVID‐19 diagnosis. During future global emergencies drug prescriptions should better be monitored in frail populations, especially in case of drugs with uncertain efficacy and safety.